2015
DOI: 10.1103/physrevb.91.180503
|View full text |Cite
|
Sign up to set email alerts
|

Surface instability in nodal noncentrosymmetric superconductors

Abstract: We study the stability of topologically protected zero-energy flat bands at the surface of nodal noncentrosymmetric superconductors, accounting for the alteration of the gap near the surface. Within a selfconsistent mean-field theory, we show that the flat bands survive in a broad temperature range below the bulk transition temperature. There is a second transition at a lower temperature, however, below which the system spontaneously breaks time-reversal symmetry. The surface bands are shifted away from zero e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…It was realized that requiring a full superconducting gap was not required to generate edge states 229,243,286,287,[293][294][295][296][297]304 . For pairing states with the same symmetry as the crystal (s-wave-like), these states appeared in the predominantly spin-triplet case.…”
Section: B Nodal Noncentrosymmetric Superconductorsmentioning
confidence: 99%
“…It was realized that requiring a full superconducting gap was not required to generate edge states 229,243,286,287,[293][294][295][296][297]304 . For pairing states with the same symmetry as the crystal (s-wave-like), these states appeared in the predominantly spin-triplet case.…”
Section: B Nodal Noncentrosymmetric Superconductorsmentioning
confidence: 99%
“…These materials lack inversion symmetry and are characterized by strong antisymmetric spin-orbit coupling (SOC), which induces a non-trivial topology for the electronic band structure 27 . This leads to the existence of helical Majorana modes, zero-energy flat-bands 15,24,28 and arc surface states 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon further cooling, the observed zero-bias peak splits into two 38,39 , which is interpreted as a sign of spontaneous TRS breaking 40 . This was examined by several MF studies [4][5][6][7][8][9] , which found that for attractive interactions the order parameter develops imaginary s-wave components near the boundary, while for repulsive interactions edge ferromagnetism (FM) is induced.…”
Section: Introductionmentioning
confidence: 99%
“…Ss, 03.65.vf, 71.27.+a, 74.20.Rp, 74.50.+r Introduction: The discovery of topological insulators 1,2 has led to the insight that nontrivial band topologies can give rise to exotic surface states [1][2][3] . Particularly interesting are topological flat-band surface states, since their large density of states enhances correlation effects [4][5][6][7][8][9][10][11][12][13][14][15] . Surface states with a (nearly) flat dispersion can occur both in topological semimetals [15][16][17] and in nodal topological superconductors (SCs) [18][19][20][21] .…”
mentioning
confidence: 99%